ON PECULIARITIES OF RADIO WAVE SCATTERING BY A SOUND PULSE IN THE ATMOSPHERE - Bryukhovetski, A. S.; Vichkan’, A. V. (Видавничий дім «Академперіодика», 2016)
PACS number: 94.20.wsPurpose: Scattering of radio waves by a sound pulse in the atmosphere is investigated theoretically.Design/methodology/approach: The asymptotic of the scattered field in the approximation of the Fresnel diffraction is analyzed using the quadratic expansion of the phase and Gaussian directional patterns of radiating systems.Findings: It is shown that for small angles of backscattering the field is determined by the focusing effects.Conclusions: Explanation of the focus by “degenerate” saddle points of the studied integrand phase is suggested.Key words: waves scattering, oscillating integral, stationary phase, “degenerate” saddle pointManuscript submitted 23.11.2015Radio phys. radio astron. 2016, 21(1): 24-36REFERENCES1. BRYUKHOVETSKI, A. S., 2014. Account for sphericity of wave phase fronts in the theory of wave scattering by turbulent atmosphere. Radio Phys. Radio Astron. vol. 19, no 3, pp. 217–228 (in Russian).2. BRYUKHOVETSKI, A. S., 1970. Scattering of electromagnetic waves in the artificially created environments. PhD thesis ed. O.Ya.Usikov Institute for Radiophysics and Electronics of NASU,Kharkiv,Ukraine (in Russian).3. BRYUKHOVETSKI, A. S., 2005. Radar reflection from acoustic pulse. Radio Phys. Radio Astron. vol. 10, no 4, pp. 432–441 (in Russian).4. KALLISTRATOVA, M. A. and KON, A. I., 1985. Radioacoustic Sensing of the Atmosphere.Moscow : Nauka Publ. (in Russian).5. KRYUKOVSKII, A. S., LUKIN, D. S., PALKIN, E. A. and RASTYAGAEV, D. S., 2006. Wave catastrophes: types of focusing in diffraction and propagation of electromagnetic waves. Radiotekhnika i Elektronika. vol. 51, no. 10, pp. pp.1155–1192 (in Russian).6. BRYUKHOVETSKI, A. S., 2013. Near-to-far zone transition in a two-point wave scattering by a statistically rough surface. Radio Phys. Radio Astron. vol. 18, no 3, pp. 244–256 (in Russian).7. TATARSKI, V. I., 1967. Wave Propagation in a Turbulent Atmosphere. Moscow: Nauka Publ. (in Russian).8. KRAVTSOV, YU. A. and ORLOV, YU. I., 1980. Geometrical Optics of i\Inhomogeneous Media. Moscow: Nauka Publ. (in Russian).9. FEDORYUK, M. V., 1987. Asymptotics: Integrals and Series. Moscow: Nauka Publ. (in Russian).10. IPATOV, E. B. and PALKIN, E. A., 1999. Investigation of Scanning and Multibeam Reflector Antennas by the Methods of the Theory of Wave Catastrophes. Radiotekhnika i Elektronika. vol. 44, no. 4, pp. 431–441 (in Russian).11. KUZ’MICHEV, V. E., 1989. Laws and formulas of physics. Directory.Kiev: Naukova Dumka Publ. (in Russian).12. PRUDNIKOV, A. P., BRYCHKOV, YU. A. and MARICHEV, O. I., 1981. Integrals and series.Moscow: Nauka Publ. (in Russian).13. FELSEN, L. B.and MARKUVITZ, N., 1978. Radiation and Scattering of Waves. Vol. 1.Moscow: Mir Publ. (in Russian).14. ABRAMOWITZ, M. and STEGUN, I. A., 1979. Handbook of Special Functions. Moscow: Nauka Publ. (in Russian).